Chronic idiopathic intussusception: an unusual cause of intestinal obstruction in adults. - Chatterjee, S; Das, KK; Gupta, S (Department of Surgery, UKM Medical Centre, 2013)
Intussusception, though common in children, occurs in adults as well, though infrequently. It constitutes only 1% of all cases of intestinal obstruction. The patients present with non-specific abdominal pain of long duration. This makes a clinical suspicion tricky and diagnosis challenging. Unless, a mass is palpable in the abdomen or the intussusception reveals itself on rectal examination, there may be little more to go on other than vague abdominal pain and nonspecific signs. Adult intussusception is associated with an underlying pathology in over 90% cases, as compared to intussusception in children, where over 90% are idiopathic. But 10% of adult cases may present with no demonstrable cause of intussusception, and are considered to have idiopathic intussusception. Preoperative diagnosis is difficult, and may be clinched by a CT scan. Therefore, a high index of suspicion is required for diagnosis of intussusception in adults. Treatment in adults differs from children and consists of resection and anastomosis with no prior attempt at reduction. We here present a case of intestinal obstruction due to chronic idiopathic intussusceptions in a 27-year-old male patient.